KETERLIBATAN MASYARAKAT DALAM PENGEMBANGAN DAN PENGELOLAAN DESTINASI WISATA GUA BATU CERMIN, DESA BATU CERMIN, KABUPATEN MANGGARAI BARAT, NUSA TENGGARA TIMUR - April, Nada; Susilowati, Linda (Universitas Kristen Satya Wacana, 2020)
Indonesia has been establishing tourism as the leading industry sector because it's 22,4% growth in 2019. The establishment of the tourism sector as the leading industry sector must be supported by good development and management. To achieve development goals, local communities must involve in the tourism sector. This research is conducted to find out the involvement of Batu Cermin Village's community on developing and managing tourist destinations. The data collection techniques used in this study are interviews and observations. From this research found that the participation of local communities in Batu Cermin Village can be categorized into five types of participation: idea contribution, work participation, expertise participation, material participation, and fund contribution. Participation of local communities in Batu Cemin is important because the accurate information is only owned by local people, besides that community trust is needed for the successful implementation of policies. There is also some supporting factor and obstacle of community involvement in Batu Cerim. The supporting factor is managerial of the which been moved to Village-Owned Enterprise (BUMDes). The obstacles to the involvement of the local community in Batu Cermin Village are the lack of knowledge about tourism issues, lack of the awareness of destination ownership, and lack of ability to see the economic opportunities.